THE IMPLICATIONS OF T.M HASBI ASH-ṢHIDDIEQY'S CRITICISM OF THE NĀSIKH-MANSŪKH THEORY IN HIS INTERPRETATION OF PLURALISM VERSES - Ummam, Naufa Izzul; Zulliandi, Yuviandze Bafri; Zarnuji, Muhdarul Islami (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2024)
The exsistence of nāsikh-mansūkh in the Qur'an frequently sparks debate among Muslim scholars. Whether or not nāsikh-mansūkh is accepted as an interpretive tool will lead to different interpretive implications. In the case of plural verses (Qs. al-Baqarah/2: 62 and Qs. al-Maidah/5: 69), the use of nāsikh-mansūkh as a tool for interpretive analysis tends to lead to the conclusion that there is no salvation for non-Muslims in the hereafter. On the other hand, not using nāsikh-mansūkh as an analysis of the interpretation of plural verses tends to lead to the conclusion that non-Muslims will still receive salvation in the afterlife. This research aims to see the implications of T.M Hasbi ash-Shiddieqy's interpretation of plural verses without considering nāsikh-mansūkh as an interpretation tool. This research is qualitative research with descriptive analysis. This research suggests that the non-use of nāsikh-mansūkh in Hasbi's interpretation does not have significant implications. The results of the interpretation he put forward are the same as those of scholars who agree with the existence of nāsikh-mansūkh in plural verses, namely that salvation in the afterlife belongs only to Muslims.